Deixis of the Song 'Lovely' by Billie Eilish ft. Khalid: A Pragmatics Study - Kurniati, Nia; Shofa, Ghefira Zahira (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This study aims to analyze the use of deixis in the lyrics of the song “Lovely” by Billie Eilish and Khalid using a pragmatic approach. Deixis, as a linguistic element whose meaning depends on context, includes five main types: person, place, time, discourse, and social deixis. The analysis shows that the song uses deixis effectively to convey a deep emotional narrative. Person deixis, through the use of I and you, stands out in creating a personal relationship between the speaker and the listener. Place and time deixis describe the space and duration of the emotional struggle, while discourse deixis provides narrative continuity. Meanwhile, social deixis, although implicit, reflects the universal relationship between the singer and the audience. The results of this study are relevant to previous pragmatic studies, supporting the idea that songs as aesthetic texts can be a powerful medium of communication. In particular, this study highlights that the use of deixis in lyrics not only functions to build context, but also to create a complex and relatable emotional experience for the listener. These findings provide important contributions to linguistic studies, education, and the analysis of musical artworks, while also opening up opportunities for pragmatic studies of other musical texts.